Weakly Humidity‐Dependent Proton‐Conducting COF Membranes - Cao, Li; Wu, Hong; Cao, Yu; Fan, Chunyang; Zhao, Rui; He, Xueyi; Yang, Pengfei; Shi, Benbing; You, Xinda; Jiang, Zhongyi (Advanced materials (Weinheim), 2020)
State‐of‐the‐art proton exchange membranes (PEMs) often suffer from significantly reduced conductivity under low relative humidity, hampering their efficient application in fuel cells. Covalent organic frameworks (COFs) with pre‐designable and well‐defined structures hold promise to cope with the above challenge. However, fabricating defect‐free, robust COF membranes proves an extremely difficult task due to the poor processability of COF materials. Herein, a bottom‐up approach is developed to synthesize intrinsic proton‐conducting COF (IPC‐COF) nanosheets (NUS‐9) in aqueous solutions via diffusion and solvent co‐mediated modulation, enabling a controlled nucleation and in‐plane‐dominated IPC‐COF growth. These nanosheets allow the facile fabrication of IPC‐COF membranes. IPC‐COF membranes with crystalline, rigid ion nanochannels exhibit a weakly humidity‐dependent conductivity over a wide range of humidity (30–98%), 1–2 orders of magnitude higher than that of benchmark PEMs, and a prominent fuel cell performance of 0.93 W cm−2 at 35% RH and 80 °C arising from superior water retention and Grotthuss mechanism‐dominated proton conduction. A bottom‐up approach based on the diffusion and solvent co‐mediated growth of covalent organic frameworks (COFs) is proposed to synthesize nanosheets of a highly crystalline, intrinsically proton‐conducting COF (IPC‐COF) in aqueous solution. The high‐quality IPC‐COF nanosheets allow the fabrication of defect‐free and robust IPC‐COF membranes that exhibit a weakly humidity‐dependent proton conduction and a prominent fuel‐cell performance.